Salvage treatment for severe upper gastrointestinal bleeding caused by Mallory-Weiss syndrome and myocardial depression after acute myocardial infarction - Yi Zhang; Hongsheng Liu; Xinmei Liu (Heliyon, 2022)
Complications related to upper gastrointestinal bleeding (UGIB) after acute myocardial infarction (AMI) and hyperkalemia-induced myocardial depression (MD) are not rare. However, severe UGIB caused by Mallory-Weiss syndrome (MWS) after AMI in patients with hyperkalemia-induced MD after red blood cell (RBC) transfusion has not previously been reported. We report a case of a 44-year-old male patient, presenting with AMI of the anterior wall, who underwent percutaneous coronary intervention (PCI). The patient developed two episodes of hematemesis within 12 h post-operation, the second of which was massive (about 2000 ml). Emergency endoscopy revealed MWS, thus titanium clips were simultaneously placed to stop the bleeding. In addition, the patient received RBC transfusion. One hour later, his blood pressure (BP) suddenly dropped to 63/35 mmHg, with arterial blood gas analyses revealing hyperkalemia. He was treated with bicarbonate, insulin and calcium gluconate to correct hyperkalemia, which lowered serum potassium and returned his cardiac function to normal. This case shows a dilemma in treatment of upper gastrointestinal bleeding caused by MWS after coronary stent implantation, suggesting the need for timely hemostatic endoscopic procedures when this happens. Clinicians are advised to monitor patients’ vital signs in order to prevent serious damage caused by transfusion-related complications. This is because complex and uncommon complications may begin with such common symptoms, which can rapidly deteriorate to life-threatening situations if not timely treated.